Relationship between career adaptability and employability skills: towards engineering graduates career development - Omar, Muhd Khaizer; Romli, Aliaa Hayati; Azeem, Nazia; Zakaria, Anis (Human Resources Management Academic Research Society (HRMARS), 2023)
A crucial component of successful career preparation among graduates is the ability to adapt to challenging industrial settings. Similarly, job-related and employability skills have become propensity assets to adapt to the volatility, uncertainty, complexity, and ambiguity (VUCA) landscape in different workplaces. Employers demand new and different employee skill sets due to technological advancement and the rapidly changing job landscape. This research seeks to determine the relationship between career adaptability and employability skills. Results based on data collected from 205 final-year engineering students at Universiti Putra Malaysia (UPM) indicate that the career adaptability and employability skills level was high. More importantly, career adaptability is positively associated with students' employability skills. This study benefits educators and policymakers by providing a detailed view of career adaptability and employability skills from the existing curriculum delivery. It also acts as a guideline for further efforts to amplify career development among graduates to ensure their employment success.